Pharmacogical Potential And Bioactivity Of Mangifera indica L.: A Scopus-Based Bibliometric Analysis - Dwi Astuti, Niken; Octaviani, Peppy; Prabandari, Rani (Yayasan Inspirasi El Burhani, 2025)
Introduction: Mangifera indica L. (mango) is a tropical plant valued in traditional medicine and rich in bioactive compounds such as mangiferin, quercetin, and catechin, known for antioxidant, anti-inflammatory, antimicrobial, antidiabetic, hepatoprotective, and immunomodulatory activities. Despite increasing research, no comprehensive bibliometric mapping of its pharmacological potential and bioactivity has been conducted. Objective: To analyze global research trends, influential contributors, and thematic foci on the pharmacological potential and bioactivity of Mangifera indica L. using a Scopus-based bibliometric approach. Method: Publications from 2015–2024 were retrieved from Scopus using defined Boolean search terms. Only English-language journal articles in the final publication stage were included, resulting in 305 records. Data were analyzed using Microsoft Excel 2021, Bibliometrix/Biblioshiny, and VOSviewer to evaluate performance indicators, thematic evolution, and network visualization of co-authorship, co-citation, and keyword co-occurrence. Kesimpulan: Annual publications peaked in 2023 (n=50) and 2024 (n=54), showing growing scholarly interest. Industrial Crops and Products was the most influential journal, strongly linked to Molecules and Food Chemistry. CASAS L and MANTELL C were the most productive authors (7 articles each), while Ho Chi Minh City University of Technology led institutional output (47 articles). India was the most prolific country and a central hub for collaborations. Keyword mapping revealed two clusters: phytochemistry and bioactivity, and methodological advances. Research on Mangifera indica L. has expanded significantly in the last decade, bridging pharmacognosy, food science, and nanotechnology. However, gaps remain in translational research and clinical application.